Rituximab modulates T- and B-lymphocyte subsets and urinary CD80 excretion in patients with steroid-dependent nephrotic syndrome. (October 2018) - Bhatia, Divya; Sinha, Aditi; Hari, Pankaj; Sopory, Shailaja; Saini, Savita; Puraswani, Mamta; Saini, Himanshi; Mitra, Dipendra; Bagga, Arvind
Abstract Background Rituximab, a monoclonal antibody targeting B lymphocytes, effectively sustains remission in steroid-dependent nephrotic syndrome (SDNS). We studied its effects on lymphocyte subsets and urinary CD80 excretion (uCD80) in patients with SDNS. Methods Blood and urine samples were collected from 18 SDNS patients before rituximab, and after 1 month and 1 year or at first relapse. T and B lymphocytes and uCD80 were determined by flow cytometry and ELISA, respectively. Results Treatment was associated with reduction in counts of Th17, Th2, and memory T cells, and increased T-regulatory (Treg) cells. The Th17/Treg ratio declined from baseline (median 0.6) to 1 month (0.2, P  = 0.006) and increased during relapse (0.3, P  = 0.016). Ratios of Th1/Th2 cells at baseline, 1 month after rituximab, and during relapse were 7.7, 14.0 (P  = 0.0102), and 8.7, respectively. uCD80 decreased 1 month following rituximab (45.5vs. 23.0 ng/g creatinine;P  = 0.0039). B lymphocytes recovered earlier in relapsers (60.0vs. 183.0 days;P  < 0.001). Memory B cells were higher during relapse than remission (29.7vs. 18.0 cells/µL;P  = 0.029). Conclusion Rituximab-induced sustained remission and B-cell depletion was associated with reduced numbers of Th17 and Th2 lymphocytes, and increased Treg cells; these changes reversed during relapses. Recovery of B cells and memory B cells predicted the occurrence of a relapse.